Evidence synthesis for environmental decision making: why “summary” is not the same as “synthesis” - Kathryn A. Monk (Indonesian Journal of Applied Environmental Studies, 2026)
Environmental science has never been more productive. Every month we see new studies on forests, fisheries, pollution, climate hazards, restoration, protected areas, and community-based management. In Indonesia and across Southeast Asia, where environmental decisions often must be made quickly amid rapid development pressure and climate risk, the idea of “evidence-informed decision making” is widely supported. But what kind of evidence are we actually using to inform these decisions? Many evidence sources look similar. They cite research. They summarise findings. They offer recommendations. Sometimes they carry authoritative branding or are published in high-impact journals. But they do not all do the same job. If we treat them as interchangeable, we risk using evidence in ways that create overconfidence, selective learning, and weak foundations for policy and practice.